African Military Aircraft Procurement from China: A Case Study from Zambia - Jyhjong Hwang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2020)
Jyhjong Hwang does a deep dive into the Zambian Air Force as a case study to explore why developing countries want to expand their air forces and why Chinese arms suppliers may be preferred. Ultimately, she finds five different logics are spurring Zambia's decisions: military and bilateral relations history, current strategic concerns in defense and finance, domestic political economy, psychological quest for prestige, and systemic concerns are all essential factors.
Keywords: 330